The peyote road: ancient religion in contemporary crisis (Berkeley Media, 1996)
This widely acclaimed, landmark documentary was instrumental in the campaign to have Congress overturn the U.S. Supreme Court's 1990 "Smith" decision, which denied the protection of the First Amendment to the traditional sacramental use of peyote by Indian people. As timely and relevant today as ever, the film examines the history of European and American religious intolerance -- especially toward indigenous peoples -- and documents the centuries-old sacramental use of the cactus Peyote in the Americas, where it is integral to the beliefs and ceremonies of one of the oldest and largest Native religions in the Western hemisphere. The film seamlessly interweaves live-action and archival film footage, historical photographs and paintings, and commentary by members of the Native American church, lawyers, and noted scholars of history, religion, and anthropology. The film demonstrates how the Court's decision ultimately threatened the religious freedom of all Americans, and chronicles the successful efforts of the American Indian Religious Freedom Coalition, including the passage of the historic 1994 Amendment to The American Indian Religious Freedom Act that legalized sacramental peyote use. "The Peyote Road" is both classic and utterly contemporary. It will engage students and will generate analysis and discussion in a variety of courses in Native American studies, religious studies and comparative religion, cultural anthropology, American history and studies, and legal studies. This version of the film includes a 1996 legislative update. It was produced by Gary Rhine and directed by Rhine and Fidel Moreno (Yaqui/Huichol) for Kifaru Productions. The film was written by Phil Cousineau and his eloquent narration is delivered by noted actor and activist Peter Coyote